The Physiological and Psychological Benefits of Dance and its Effects on Children and Adolescents: A Systematic Review - Tao, Dan; Gao, Yang; Cole, Alistair; Baker, Julien S.; Gu, Yaodong; Supriya, Rashmi; Tong, Tomas K.; Hu, Qiuli; Awan-Scully, Roger (Frontiers in Physiology, 2022)
Background: The aim of this review was to examine the physiological and psychological benefits of dance and its effects on children and adolescents. We consider the therapeutic benefits of dance and outline the potential of dance as an alternative therapy for certain pathologies and medical disorders. Secondly, we summarize the types of dances used in physical interventions, and comment on the methodologies used. Finally, we consider the use of dance as a different exercise modality that may have benefits for increased physical activity generally, and for increased physical education provision in schools. Methods: A structured search strategy was conducted using the databases of PubMed, MEDLINE, Web of science, PsycARTICLES, and Social Science database. This review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews. Studies that were published in the past 20 years were considered for inclusion. All written publications were searched for in English, and all articles included in this review were peer reviewed full papers. Conclusion: The key findings from this review indicate that dance is a feasible alternative to traditional physical activity. The findings also indicate that dance provides physiological and psychological benefits to healthy and medically compromised populations. Implementation of dance programs in schools and society generally needs serious consideration by policy makers. We hope that the results of this review stimulate debate and provide the necessary evidence to profile dance as a viable alternative medium of physical activity. Comprehensive and integrated changes will be needed including economical and legislative support from politicians and associated governmental agencies. The findings reported here are important and have implications for health policy change, reconfiguration, and implementation.